SELF-ASSESSMENT: THE ROLE OF PSYCHOLOGY IN PERSONAL DEVELOPMENT (Лучшие интеллектуальные исследования, 2025)
Abstract; This article explores the concept of self-assessment and its importance in the context of personal development. Drawing from contemporary psychological theories, it analyzes how self-evaluation contributes to self-awareness, goal setting, and behavioral change. The article also discusses the influence of cognitive and emotional factors on accurate self-assessment and suggests practical strategies to enhance it through psychological interventions.